Age- and Gender-Specific Prevalence of Risk Factors in Patients with First-Ever Ischemic Stroke in China - Xiao-ying Yao; Yan Lin; Jie-li Geng; Ya-meng Sun; Ying Chen; Guo-wen Shi; Qun Xu; Yan-sheng Li (Stroke Research and Treatment)
Background. Evidences are accumulating that age and gender have great impact on the distribution of stroke risk factors. Such data are lacking in Chinese population. Methods. 1027 patients with first-ever ischemic stroke (IS) were recruited and divided into young adult (<50 years), middle-aged (50∼80 years), and very old (>80 years) groups according to stroke onset ages. Vascular risk factors were collected and compared among groups. Results. Female patients were globally older than male patients at stroke onset and having higher prevalence of diabetes mellitus (DM), heart diseases, and atrial fibrillation (AF). However, females were less likely to drink heavily or smoke than males. Young patients had a much higher proportion of smoking and drinking than middle-aged and very old patients and the highest family history of hypertension, while very old patients had the highest prevalence of heart diseases and AF but lowest proportion of positive family history of vascular diseases. Hypertension and DM were equally frequent among three groups. Conclusion. Our study showed that vascular risk factors had a specific age and gender distribution pattern in Chinese IS patients. Secondary prevention strategy should emphasize on the control of different risk factors based on patient’s age and gender.